Analysis of marine dietary supplements using NMR spectroscopy1. Issue 12 (21st June 2015) - Dais, Photis; Misiak, Maria; Hatzakis, Emmanuel
<x xml:space="preserve">Abstract</x> The objective of this study is the qualitative and quantitative analysis of encapsulated fish oil supplements by utilizing high-resolution multinuclear (1H, 13C, 31P) and multidimensional NMR spectroscopy.